Mitochondrial Dynamics in Adult Cardiomyocytes and Heart Diseases - Li, Anqi; Gao, Meng; Jiang, Wenting; Qin, Yuan; Gong, Guohua (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are the powerhouse organelles of cells; they participate in ATP generation, calcium homeostasis, oxidative stress response, and apoptosis. Thus, maintenance of mitochondrial function is critical for cellular functions. As highly dynamic organelles, the function of mitochondria is dynamically regulated by their fusion and fission in many cell types, which regulate mitochondrial morphology, number, distribution, metabolism, and biogenesis in cells. Mature rod-shaped cardiomyocytes contain thousands of end-to-end contacted spheroid mitochondria. The movement of mitochondria in these cells is limited, which hinders the impetus for research into mitochondrial dynamics in adult cardiomyocytes. In this review, we discuss the most recent progress in mitochondrial dynamics in mature (adult) cardiomyocytes and the relationship thereof with heart diseases.